Biochar filtration of drug-resistant bacteria and active pharmaceutical ingredients to combat antimicrobial resistance - Paul-Enguerrand Fady; Alexandra K. Richardson; Leon P. Barron; A. James Mason; Roberto Volpe; Meredith R. Barr (Scientific Reports)
Abstract Antimicrobial resistance (AMR) is a major cause of death worldwide, with 1.27 M direct deaths from bacterial drug-resistant infections as of 2019. Dissemination of multidrug-resistant (MDR) bacteria in the environment, in conjunction with pharmapollution by active pharmaceutical ingredients (APIs), create and foster an environmental reservoir of AMR. Creative solutions are required to mitigate environmental AMR, while taking into consideration other aspects of the planetary “Triple Crisis” of pollution, biodiversity loss, and climate change. Waste lignocellulosic biomass (LCB), a byproduct of agriculture and forestry, is the largest stream of non-edible biomass globally. Through pyrolysis, waste LCB can be converted into biochars, which have excellent attributes for adsorption of pollutants–though no studies have yet reliably correlated production conditions with efficacy, nor considered adsorption of human pathogens. By leveraging a bespoke pyrolysis reactor with precisely controlled parameters, we show that production conditions substantially affect sequestration of clinical bacterial isolates, removing up to 94% of Pseudomonas aeruginosa RP73 and 85% of Staphylococcus aureus EMRSA-15. In addition, we show that chars produced at higher peak pyrolysis temperatures (450 °C) can remove up to 88% of the antibiotic clarithromycin from wastewater, as well as significant proportions of many other APIs with varied physicochemical characteristics. These findings provide a first-in-kind insight into how production conditions affect the ability of biochars to mitigate environmental AMR.